Academic motivation in adolescents: the role of parental autonomy support, psychological needs satisfaction and self-control - Çelik, Oğuzhan (Frontiers in Psychology, 2024)
Background: Various perspectives on the existence and degree of motivation, which is a crucial factor influencing human behavior, have been studied for many years. Especially in adolescence, a phase marked by rapid change, motivation plays a crucial role in supporting young people to achieve their goals, fulfill their responsibilities, and experience healthy development.The present study aims to investigate the structural relationships among perceived parental autonomy support, satisfaction of psychological needs, self-control, and academic motivation.The study was conducted with a total of 427 high school students, including 230 females and 197 males, aged between 14 and 19 (M= 15.82; SD= 1.02).Method: Participants completed self-report measures of academic motivation, parental autonomy support, psychological needs satisfaction, and self-control. Structural equation modeling was performed to explore complex relationships between variables of interest.The study revealed that psychological needs satisfaction increased as parental autonomy support increased, and self-control also increased with the satisfaction of psychological needs. It was also found that satisfaction of psychological needs was positively related to both intrinsic and extrinsic motivation. Additionally, self-control was associated with increased intrinsic motivation and decreased amotivation. In addition, it was found that parental autonomy support has an indirect relationship with academic motivation through the satisfaction of psychological needs and self-control.It is believed that these connections will lead to a deeper understanding of the significant processes in adolescence and serve as a foundation for developing and implementing psycho-educational interventions related to these variables.